2019
DOI: 10.1007/s10531-019-01880-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative responses of spiders and plants to maritime heathland restoration

Abstract: Assessment of habitat restoration often rely on single-taxa approach, plants being widely used. Arthropods might yet complement such evaluation, especially in hard, poorly-diversified environments such as maritime clifftops. In this study we compared the responses of spiders and plants (both at species and assemblage levels) to increasing time of heathland restoration. Sampling took place in different sites of Brittany (Western France), using a replicated design of both pitfall traps and phytosociological rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 67 publications
1
18
0
Order By: Relevance
“…These sites were selected for they are all comparable with similar dominant vegetation (a short and dry heathland dominated by Erica spp . and Ulex spp ), and under ongoing ecological passive restoration with 3 degradation states by site (see full description of study sites and pictures in Hacala et al 2020).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These sites were selected for they are all comparable with similar dominant vegetation (a short and dry heathland dominated by Erica spp . and Ulex spp ), and under ongoing ecological passive restoration with 3 degradation states by site (see full description of study sites and pictures in Hacala et al 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Environmental variables where inferred from the vegetation communities using Ellenberg's index values (1992) extracted from Hill et al (2004) and corrected for the British Isles. Anthropogenic degradation was assessed by using bare ground as a proxy of degradation intensity (Hacala et al 2020). Pitfall samples were sorted in laboratory, arthropods transferred to ethanol 70°, and stored at the University of Rennes 1.…”
Section: Sampling and Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…La Pointe de l'Enfer (S2) (47°37'18.3"N 3°27'46.9"W) was degraded by frequent vehicle access and human trampling. L'Apothicairerie (S3) (47°21'44.0" N, 3°15'34.9" W) was heavily degraded by infrastructures (car park and hotel) that were removed in 2012 (see Hacala et al, 2020 for a full description, and pictures, of the sampling sites).…”
Section: Study Sitesmentioning
confidence: 99%
“…Studies in other parts of the world that have assessed how grassland restoration affects spiders found mixed results. For example, while multiple studies have found that grassland restoration affects spider abundance, richness, and diversity [ 21 , 28 , 29 , 30 , 31 ], the direction of effects vary, with some studies finding positive effects and others finding negative ones. Other studies have found no effect of restoration on spider abundance, richness, and diversity [ 28 , 30 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%